Germination and health quality of mucuna white and black seeds used as a green manure in Quevedo, Ecuador - Garcés Fiallos, Felipe (2012)
The objective was to evaluate the germination and sanitary quality of mucuna (Stizolobium spp.) white and black used as green manure in Quevedo, Ecuador. The experiment was conducted at the Laboratory of Environmental Microbiology and Plant, Universidade Técnica Estatal de Quevedo-UTEQ. The seeds of mucuna white and black were from the experimental field in La María 2010 harvest. The work consisted of two treatments for each type of seed of mucuna (white and black), totaling four. In each Petri plates were plated five (5) seeds, ten (10) plates per treatment, totaling 50 in each. Transferred to a growth chamber (incubator) control temperature of 25 °C ± 2 without photoperiod. We evaluated the physiological quality (germination for six days and rate (r) of growth of the radicle) and health (incidence of pathogens) its seeds. The germination was between 68 (BDA medium) and 40% (filter paper) for white velvet, among both black velvet, half were between 70 (BDA medium) and 34 (paper). The pathogens found in seeds of white and black velvet, were the fungi Fusarium sp., Aspergillus sp., Penicillum sp., as well as an unidentified bacterium, with averages for each of 10, 29, 30 and 33% incidence, respectively.